Sjögren's syndrome comes of age (1999)
Primary Sjögren's syndrome (SS) is an autoimmune exocrine disease characterized by salivary and lacrimal gland destruction progressing to xerostomia and xerophthalmia (sicca symptoms). Nevertheless, any exocrine as well as nonexocrine organ may be involved. Dryness is not solely a result of glandular destruction; cytokines, autoantibodies, and other soluble factors may be also involved. We propose a two-stage model of SS pathogenesis in which the initial process seems to be increased epithelial cell apoptosis leading to autoantibody production and subsequent salivary gland lymphocytic infiltration. Treatment of SS includes education, prevention, tears and saliva substitution, exocrine glands stimulation, and immunointervention. Pilocarpine, a natural alkaloid and stimulator of muscarinic receptors in exocrine glands, is an effective agent for the treatment of sicca symptoms. Another systemic stimulatory agent to treat sicca symptoms is cevimeline, a quinuclidine derivative of acetylcholine that exhibits high affinity for the muscarinic M3 receptor which is located on lacrimal and salivary gland epithelium. Molecular understanding of the biological mechanisms that lead to tissue damage in SS may lead to newer biological treatment for this common, disabling and at times devastating illness.